2013
DOI: 10.1111/cch.12102
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term improvements in oral communication skills and quality of peer relations in children with cochlear implants: parental testimony

Abstract: The results highlight the need for more specific examination of various developmental periods in combination with the progress of oral communication and peer relationships among children with implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 60 publications
0
4
1
1
Order By: Relevance
“…Apparently, they do not seem to face communication problems in the school. This contrasts with the findings from mainstream schools where students with CI, despite their generally good psychosocial adjustment , were not socially integrated to the same extent as their hearing peers, sometimes facing communication challenges via oral language (Bat-Chava, Martin, & Imperatore, 2014;Damen, Langereis, Snik, Chute, & Mylanus, 2007;Mukari, Ling, & Ghani, 2007;Rich et al, 2013;Wu et al, 2013). Previous studies indicated that several factors play a role in the latter outcome, such as the ability of school personnel in the mainstream schools to adapt to the special needs of the students with CI, the lack of support services, and so forth (Jachova & Kovacevic, 2010).…”
Section: Research Questioncontrasting
confidence: 90%
“…Apparently, they do not seem to face communication problems in the school. This contrasts with the findings from mainstream schools where students with CI, despite their generally good psychosocial adjustment , were not socially integrated to the same extent as their hearing peers, sometimes facing communication challenges via oral language (Bat-Chava, Martin, & Imperatore, 2014;Damen, Langereis, Snik, Chute, & Mylanus, 2007;Mukari, Ling, & Ghani, 2007;Rich et al, 2013;Wu et al, 2013). Previous studies indicated that several factors play a role in the latter outcome, such as the ability of school personnel in the mainstream schools to adapt to the special needs of the students with CI, the lack of support services, and so forth (Jachova & Kovacevic, 2010).…”
Section: Research Questioncontrasting
confidence: 90%
“…The results confirmed that, especially regarding their relationships with others, adolescence may represent a particularly difficult period for adolescents with hearing problems, who are aware of being at a disadvantage relative to their peers (Tomassini, 1999). Several studies have indeed indicated the difficulties that adolescents with hearing problems encounter, including difficulties in developing friendships with hearing peers, lower levels of social competence, increased levels of loneliness (Most et al, 2012), and lower conversational skills, which can lead to difficult interactions with others (Bat-Chava et al, 2014). As regards the lower level of aversion toward aloneness, perhaps adolescents with CIs feel less negative about being on their own because they are more used to it and so, perhaps, it does not loom large as a problem.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several studies have indicated various benefits and advantages of using CIs. In addition to improved language ability, progress has been identified in socio-emotional skills (Bat-Chava et al, 2014), quality of life (Faber and Grøntved, 2000), and self-concept (Moog et al, 2011). Moreover, although many studies have hypothesized that deaf adolescents are at risk of developing psychological disorders, the empirical evidence is not so consistent, with some studies suggesting that the socio-emotional development of these adolescents is comparable with that of their hearing peers (Yucel and Sennaroglu, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Certain domains of psychosocial functioning may be at higher risk in CI users compared with typically developing normal-hearing (NH) children (Dammeyer 2009; Punch & Hyde 2011), suggesting that characteristics associated with a period of early deafness, language delay, and subsequent cochlear implantation present significant challenges to these critical areas of development. For example, many pediatric CI users find forming friendships, socializing with peers, and exerting emotional control to be challenging (Bat-Chava et al 2005, 2013; Dammeyer 2009; Huber 2005; Punch & Hyde 2011).…”
Section: Introductionmentioning
confidence: 99%